Effect of steam explosion pretreatment method in pulp production on pilot scale - Muhammad Arif Fahmi, Supian; Khairatun Najwa, Mohd Amin; Shahril, Mohamad; Saidatul Shima, Jamari (Universiti Malaysia Pahang, 2018)
The study on pulp production at a pilot scale and the implementation of steam explosion pretreatment in the process. The pulp production using the physic-chemical process that includes steam explosion pretreatment and mild alkaline treatment. The physicochemical and morphological characteristics, elemental composition and size distribution of the fiber were characterized using the scanning electron microscope (SEM), thermogravimetric analysis (TGA), X-ray Diffraction (XRD) and Fourier transform infrared (FTIR). The difference on the morphology of the raw and exploded can be clearly seen when the smooth structure of raw fiber turn ruptured and the size decreases from 213.6μm to 9.5μm. FTIR and TGA analysis provided clear evidence from the peak of lignin and hemicellulose were decreasing from the raw to the exploded fiber and pulp. The crystallinity of the fiber changes when treated. Thus, pulp can be produced in a large scale by using the steam explosion treatment.